Exploring Nazahah’s Mediation in Reinforcing Consumer Trust among Micro Scale Nasi Kuning Enterprises - Wahyuni, Sri; Syaparuddin Razak (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study investigates the mediating role of nazāhah conceptualized as integrity, honesty, and purity of intention in strengthening consumer trust among micro-scale nasi kuning enterprises in Bone Regency, Indonesia. Grounded in Islamic Business Ethics Theory and Consumer Trust Theory, the research examines how ethical selling behavior, compliance with Islamic values, and business social responsibility influence consumer trust through the internalization of nazāhah. Using a quantitative explanatory design, data were collected from 150 respondents and analyzed using PLS-SEM. The results demonstrate that nazāhah has a strong and significant direct effect on consumer trust, while also fully mediating the relationships between social responsibility and trust, as well as indirectly linking ethical and religious values to trust formation. These findings indicate that ethical awareness and Sharia compliance alone are insufficient to generate trust unless they are transformed into consistent moral conduct through nazāhah. The study contributes to the literature by empirically positioning nazāhah as a strategic ethical mechanism that bridges spiritual values and market behavior. Practically, the findings highlight the importance of integrity-based education and socially responsible practices in fostering sustainable trust within Islamic micro-enterprises.